1991
DOI: 10.1177/036354659101900511
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord concussion in rugby players

Abstract: During an analysis of a group of 40 rugby players who had sustained cervical spinal cord injury, 9 players were identified who had sustained only transient paralysis. These players showed no radiologic evidence of any injury to the cervical spine. We did a retrospective analysis of the clinical and radiological findings in this group of rugby players. The cervical spine radiographs were analyzed for evidence of spinal stenosis, congenital anomalies, and degenerative disk disease. Using the ratio method of asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…The significant difference in neck circumference between backs and forwards (Table I) might be considered a contributory factor to the differences in ACROM, although Pearl and Mayer (1979) reported that neck girth made no difference in neck movement in young American Football players. The factors underlying this difference between forwards and backs have yet to be elucidated, although it is likely to result from greater muscular resistance and/or cumulative musculoskeletal deterioration that has been identified in radiographic studies (O'Brien, 1996;Scher, 1990Scher, , 1991Torg & Pavlov, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The significant difference in neck circumference between backs and forwards (Table I) might be considered a contributory factor to the differences in ACROM, although Pearl and Mayer (1979) reported that neck girth made no difference in neck movement in young American Football players. The factors underlying this difference between forwards and backs have yet to be elucidated, although it is likely to result from greater muscular resistance and/or cumulative musculoskeletal deterioration that has been identified in radiographic studies (O'Brien, 1996;Scher, 1990Scher, , 1991Torg & Pavlov, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Transient contact may be induced by primary or secondary spinal canal stenosis, relaxation of the ligament of the spinal column, 8 and/or hyperextensive motion that causes the posterior longitudinal ligament and the ligamentum flavum to thicken, the dural diameter to decrease in size and the diameter of the spinal cord to increase in size. 4 There was also a report suggesting that compression of the spinal cord during hyperextension by infolding of the laminar ligaments resulted in narrowing of the spinal canal. 7 Groat et al 19 emphasized the possibility of a functional block of neural activity.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its rare incidence, there have been few reports concerning spinal cord concussion in English literatures and no reports in Japanese. [1][2][3][4][5][6] Previous reports of spinal cord concussion conclude that sports and falls were the leading cause of the injury, and that the most common site affected was the cervical or thoracolumbar junction among young subjects. There was controversy whether pre-existing abnormalities of the spine, such as spinal canal stenosis, can be a risk factor for the occurrence of spinal cord concussion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] The most frequently injured vertebrae are C4 to C6. 1 7 Approximately half of all cervical spine injuries in rugby result in tetraplegia.…”
Section: Discussionmentioning
confidence: 99%